2015
DOI: 10.1145/2782759.2782769
|View full text |Cite
|
Sign up to set email alerts
|

Planning sightseeing tours using crowdsensed trajectories

Abstract: We present an application where semantically enriched trajectories obtained from crowdsensed data are used to build an advanced system for planning personalized sightseeing tours, called TripBuilder. The interesting feature of TripBuilder is that it uses Wikipedia content and trajectories of previous tourists collected by georeferenced Flickr photos in a complex spatio-temporal framework. The objective is to address, in an unsupervised way, the problem of suggesting a budgeted sightseeing tour based on the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Geospatial big data in social media is used for analyzing and visualizing various aspects related to the urban space. Studies have shown the contribution of crowdsourced geotagged photos for diverse applications, for example, mapping areas that are more calm and more exciting by using big data of geotagged images and audio samples [7], extracting landmarks from geotagged photos by using deep neural network [8], computing pleasant (beautiful and happy) routes in Boston and London [9], and tourism route planning [10,11]. Photography is strongly related to tourism experience [12], meaning that most tourists take photos for documentation purposes as a proof of consuming the experience of travelling a city [4], such that tourism photography is correlated with tourism development [13].…”
Section: Related Researchmentioning
confidence: 99%
“…Geospatial big data in social media is used for analyzing and visualizing various aspects related to the urban space. Studies have shown the contribution of crowdsourced geotagged photos for diverse applications, for example, mapping areas that are more calm and more exciting by using big data of geotagged images and audio samples [7], extracting landmarks from geotagged photos by using deep neural network [8], computing pleasant (beautiful and happy) routes in Boston and London [9], and tourism route planning [10,11]. Photography is strongly related to tourism experience [12], meaning that most tourists take photos for documentation purposes as a proof of consuming the experience of travelling a city [4], such that tourism photography is correlated with tourism development [13].…”
Section: Related Researchmentioning
confidence: 99%
“…Researchers aim to discover comprehensive tourism routes from user-generated information by using the calculated POI geographic information to guide photographers to locations that demonstrate tourism features (e.g., Lim (2015), Li et al, (2015), Choudury et al, (2010), andYahi et al, (2015)). Yahi et al (2015), Brilhante et al, (2015), and Mor and Dalyot (2018), for example, use Google Maps API to compute routes between POIs, while Sun et al (2015) use the Dijkstra algorithm with weighted popularity road matrix to compute the routes. Chen et al, (2017) enriched the road network with scenic score considering density and dominate direction of geotagged photos and check-ins near each segment.…”
Section: Related Workmentioning
confidence: 99%
“…Becker et al (2015) extracted photo trails for a single photographer, regardless of the time span, by comparing the extracted trail to a weighted POI geographic layer to explore tourists' patterns. Ali et al (2013) and Choudhury et al (2010) analyze photographers' pattern by a comprehensive study of their photo sequence to evaluate tourism routes, while Brilhante et al (2015) used Wikipedia POIs information to analyze crowdsourced tourism trajectories. To extend these approaches, we aim to generate comprehensive tourism routes by investigating and interpreting the accumulated trajectory patterns of the tourism-photographers, without relying on external POIs information.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…While many studies recognize that explorations of meaningful spots in destinations are a primary task in itinerary planning and intelligent transportation [9][10][11], movement as a tour experience and pedestrian mobility based on qualitative factors, except for the shortest route principle, tend to be underestimated [12]. Some research on the automatic generation of a tour itinerary has proposed movement routes based on time saving or querying Google Maps [13][14][15][16]. From the perspective of walking tours, they only take access into account, not all factors in the policy of route selection.…”
Section: Introductionmentioning
confidence: 99%